Perception of Official Corruption, Satisfaction With Government Performance, and Subjective Wellbeing—An Empirical Study From China - Ma, Jiazheng; Guo, Bin; Yu, Yanghang (Frontiers in Psychology, 2022)
Both corruption and subjective wellbeing are of concern to academics and governments. Although some evidence suggests that corruption deteriorates subjective wellbeing, the relationship between perception of official corruption and subjective wellbeing is still unknown. This study aims to examine the link between perceived official corruption and subjective wellbeing in the context of China and whether satisfaction with government performance has a mediating effect in the process. Based on data from China General Social Survey, a structural equation model was used to test the hypotheses. The results of 3,033 Chinese respondents suggest that perception of official corruption is negatively related to subjective wellbeing, and satisfaction with government performance plays a mediating role in the relationship between perception of official corruption and subjective wellbeing.